Influence of obese phenotype on metabolic profile, inflammatory mediators and stemness of hADSC in adipose tissue - Rawal, Komal; Patel, Tushar P.; Purohit, Kishan M.; Israni, Kashish; Kataria, Vyakhaya; Bhatt, Hiren; Gupta, Sarita (Clinical nutrition (Edinburgh, Scotland), 2020)
Unhealthy dietary practices, sedentary life style and lack of physical exercise in developing countries like India are major contributors of metabolic syndrome like obesity and diabetes. Obesity in Indians is defined at Body Mass Index (BMI, kg/m2) >25 and characterized as metabolically obese. A preliminary study performed to explore ramification of obesity on metabolic profile of adipose tissue and adipose derived stem cells (ADSC) from control and obese Indians. Adipose tissue/lipoaspirates from both control (BMI ≤ 23) subjects, and non-diabetic obese Indians subjects (BMI ≥ 25), were scrutinized for expressions of lipogenic genes, inflammatory mediators, stored adipokine levels, and insulin signaling proteins. Further, hADSC were isolated and immune-phenotyped from both the subject groups. Comparative assessments between chADSC and ohADSC were carried out for growth kinetics, expressions of pluripotent genes, adipogenic transcriptional factors, RUNX2, inflammatory mediators (IM), insulin signaling proteins, adipogenic and osteogenic differentiation. Adipose tissue of obese subjects depicted high leptin and resistin levels with reduced adiponectin levels. Expressions of IM and insulin signaling proteins were elevated compared to those of control subjects. hADSC of obese subjects demonstrated diminished proliferation, altered pluripotent genes, aggravated inflammation, adipogenesis with reduced osteogenesis. hADSC of obese had established insulin resistance compared to those of control subjects. This is the first study that describes hADSC of metabolically obese Indians have insulin resistance at lower BMI compared to Caucasians exemplifying plausible role in diminishing stemness of hADSC. Study alarms Indians to restore healthy dietary habits and assess quality of hADSC in regenerative therapy. •First comparative study on hADSC in metabolically obese Indians.•hADSC of obese committed to adipogenic lineage, reduced osteogenesis.•hADSC of obese Indians have insulin resistance, reduced MYF5, 1st population study.•High levels of inflammatory markers in hADSC and adipose tissue of obese.•Altered stored adipokines and lipogenic genes of adipose tissue in Indian obese.